The relationship between job satisfaction and organizational commitment - Chon, Siu Mei (Universiti Malaysia Sarawak (UNIMAS), 2019)
This study aims to identify the relationship between job satisfaction and organizational commitment. The quantitative methodology was used for this research. A total of one hundred and fifty set questionnaires were distributed to respondents by using random sampling method. There were one hundred and two set of questionnaires had been returned. The finding showed that no significant difference in organizational commitment among the employees in Kuching Water Board based on different genders, age groups and marital status groups. Whereas, job satisfaction has a significant relationship and weak positive correlation with organizational commitment among the employees in Kuching Water Board. Hopefully, the findings from this research will be beneficial for future researchers to better understanding the relationship between job satisfaction and organizational commitment. Besides, this research is also useful for the organization and human resource practitioners to identify the appropriate method to increase organizational commitment of employees in an organization.